GIS-based modelling of landslide and debris flow hazard in mountainous terrain of Agra Khola watershed, central Nepal - Thapa, P. B.; Esaki, T.; Upreti, B. N. (Journal of Nepal Geological Society, 2006)
A comprehensive GIS-based analytical approach was followed to derive a spatial database of landslides and debris flows in the Agra Khola watershed of central Nepal which suffered from the hydrological disaster of 1993. For this purpose, the landslides and debris flows occurring in that area between 1993 and 2006 were delineated. From the database, the influence of geological and geomorphic variables was quantified and a spatial prediction model for landslide and debris flow hazard was worked out. In this process, quantitative statistical analysis (bivariate, multivariate) as applied to predict elements or observations between stable and unstable zones. The predicted results were classified into various hazard levels m a hazard map and were validated by comparing it with the landslide and debris flow distribution map of the Agra Khola watershed. Also the GIS-based hazard prediction model has objectivity in the procedure and reproducibility of the results in the mountainous terrains.